2020
DOI: 10.1038/s41393-020-00548-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability, and preliminary efficacy of a handcycling high-intensity interval training program for individuals with spinal cord injury

Abstract: Study Design: Pilot non-randomized clinical trial Objectives: To examine the feasibility, acceptability and preliminary efficacy of performing handcycling high intensity interval training (HIIT) for six weeks in wheelchair users with spinal cord injury. Setting: Participant’s home Methods: Participants completed pre and post graded exercise stress tests, exercise surveys and six weeks of handcycling HIIT. The HIIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
(19 reference statements)
0
8
0
1
Order By: Relevance
“…All of the studies were conducted in home/community settings. Study designs include single group intervention design (13,14), randomized clinical trials (15)(16)(17)(18)(19)(20)(21)(22), or multisite randomized clinical trials (23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the studies were conducted in home/community settings. Study designs include single group intervention design (13,14), randomized clinical trials (15)(16)(17)(18)(19)(20)(21)(22), or multisite randomized clinical trials (23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were conducted on wheelchair users with spinal cord injuries (SCI) (13,14,16,17,20,21,(23)(24)(25)(26), Three studies had participants with immobility due to any disorder (15,18,27), one study involved persons with multiple sclerosis (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIIT training, referred to in the work "physiological and mechanical response to the specific intermittent activity of calcium" consisted of half an hour of pedalling at alternating speed, 1 minute to 60 / 70% of VO2Max as active recovery and 30 seconds at 110/120% of VO2Max (Koontz et al, 2021). Endurance training (Federici et al, 2019) consisted of 2 continuous hours of pedalling at a constant speed between 70 and 80% of maximum power.…”
Section: Experimental Designmentioning
confidence: 99%
“…It is important to know the numbers and reasons for drop out during the training period and to characterize the differences between participants who do and do not drop out. Previous studies on exercise interventions have reported various reasons for dropping out: the most common being medical and motivational [7][8][9][10][11]. However, these exercise interventions consisted mostly of supervised training sessions in contrast to the freeliving training in the HandbikeBattle study.…”
Section: Introductionmentioning
confidence: 99%